How do Islamic religious education students understand the relationship between science and religion? - Subagiya, Bahrum (TAWAZUN: Jurnal Pendidikan Islam, 2025)
This study aims to map the perceptions of students of the Islamic Education Study Program at Ibn Khaldun University of Bogor regarding the relationship between science and religion and analyze the influence of demographic factors on these perceptions. The research used a field research approach with a survey method through a questionnaire distributed to 155 6th semester students in the range of 2023-2025, with a simple random sampling technique. The data were analyzed based on four typologies of science and religion relations, namely pro-religion conflict, pro-science conflict, independent, and harmonious. The results showed that almost all respondents were at a high level in the pro-religious conflict typology, which indicates the strong position of religion as the main truth reference. In the harmonious typology, about two-thirds of students were in the high category, indicating an integrative tendency between science and religion. Meanwhile, in the independent and pro-science conflict typologies, the majority of students are at a moderate level, indicating a neutral and not yet fully assertive attitude. The findings also showed that the factors of gender, educational background, and school origin did not provide significant differences in perception. This study concludes that PAI students tend to view the relationship between science and religion in a normative-religious manner, with a tendency to be harmonious, and place religion as the main epistemological framework in addressing science. Abstrak Penelitian ini bertujuan untuk memetakan persepsi mahasiswa Program Studi Pendidikan Agama Islam Universitas Ibn Khaldun Bogor mengenai hubungan antara sains dan agama serta menganalisis pengaruh faktor demografis terhadap persepsi tersebut. Penelitian menggunakan pendekatan lapangan (field research)  dengan metode survei melalui kuesioner yang disebarkan kepada 155 mahasiswa semester VI pada rentang tahun 2023–2025, dengan teknik simple random sampling. Data dianalisis berdasarkan empat tipologi relasi sains dan agama, yaitu konflik pro-agama, konflik pro-sains, independen, dan harmonis. Hasil penelitian menunjukkan bahwa hampir seluruh responden berada pada tingkat tinggi dalam tipologi konflik pro-agama, yang menandakan kuatnya posisi agama sebagai rujukan kebenaran utama. Pada tipologi harmonis, sekitar dua pertiga mahasiswa berada pada kategori tinggi, menunjukkan adanya kecenderungan integratif antara sains dan agama. Sementara itu, pada tipologi independen dan konflik pro-sains, mayoritas mahasiswa berada pada tingkat sedang, yang mengindikasikan sikap netral dan belum sepenuhnya tegas. Temuan juga menunjukkan bahwa faktor jenis kelamin, latar belakang pendidikan, dan asal sekolah tidak memberikan perbedaan persepsi yang signifikan. Penelitian ini menyimpulkan bahwa mahasiswa PAI cenderung memandang relasi sains dan agama secara normatif-religius, dengan kecenderungan harmonis, serta menempatkan agama sebagai kerangka epistemologis utama dalam menyikapi sains.